Mitigation of Psychological Impacts Caused by Landslide Disasters - Maria Fransina Febriyanti Lekekasa; Yeni Damayanti; R. Pasifikus Christa Wijaya (Journal of Health and Behavioral Science, 2026)
The landslide disaster in Amanuban Village, Oebufu, caused significant losses, including the loss of land and homes, as well as damage to infrastructure. This study employs a case study approach. Data were collected through semi-structured interviews and document review, and then analyzed using thematic analysis. Based on the research findings, the community experienced psychological impacts in the form of stress and trauma. The disaster mitigation measures implemented included relocation, which involved providing relocation housing and moving residences; emotional support in the form of empowering fellow survivors; strengthening social cohesion through mutual aid and role-sharing; and enhancing disaster resilience through public awareness campaigns, outreach, education, disaster training, and disaster simulations. The objective of these mitigation efforts is to reduce the risk of loss of life, loss of property, loss of housing, and to prevent psychological impacts.